The early bird catches the worm: an empirical analysis of imprinting in social entrepreneurship - Petra Dickel; Monika Sienknecht; Jacob Hörisch (Journal of Business Economics, 2020)
Understanding the antecedents of social entrepreneurship is critical for unleashing the potential of social entrepreneurship and thus for tackling social problems. While research has provided valuable insights into imprinting of the conventional entrepreneur, research on differences between social and conventional entrepreneurship suggests that social entrepreneurs evolve differently. Using survey data of 148 social entrepreneurs, we draw on the concepts of imprinting and critical incident recognition as a framework for understanding how social entrepreneur's childhood experiences and parental exposure to social entrepreneurship affect social entrepreneurial activity in adulthood. First, our results suggest that social entrepreneurs are imprinted by their childhood experiences but not by parental exposure to social entrepreneurship. Second, imprints tend to persist over time when they are linked to critical incidents regarding social entrepreneurship. These insights contribute to a deeper understanding of imprinting mechanisms in social entrepreneurship contexts and highlight the importance of making examples of social entrepreneurship tangible to children.
Keywords: L26; L31; 650; Social entrepreneurship; Imprinting; Childhood; Critical incidents